ANALISIS PENGGUNAAN DIKSI PADA PASAL 480 TENTANG POLEMIK RANCANGAN UNDANG-UNDANG KUHP (RUU KUHP) DI INDONESIA - Ririn Indraswari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Indonesia Timur, 2019)
The rejection of the RKUHP is voiced throughout the country. In the demands of students, the RKUHP was canceled. The emergence of RKUHP became a controversy so there was a lot of resistance from the community. One of the bills is expanding the definition of rape. In RKUHP, rape occurs as long as there is male to female violence.